An Experimental Study on Surveillance Robot Using Raspberry Pi - Soroosh Mahmoodi; Malala Stembinkosi Shapola; Parisa Hamedia (Annals of Robotics and Automation - Peertechz Publications, 2022)
Recently, robots have been developed to reduce human resources and observation time in a fast, booming, and rapidly growing technology. In this study, a surveillance robot is designed and manufactured to move around a given surrounding, preferably a domestic environment, record video & audio and send the information to the user through a network. The robot is allowed to be controlled wirelessly using Raspberry Pi technology from a location remotely using IoT technology. This sensor-based robot uses the Raspberry Pi with Ethernet, WI-Fi and Bluetooth for networking purposes. Python is chosen as the programming language in both autonomous and semi-autonomous modes. The manufactured robot was experimentally tested. The recorded videos, images and audio are successfully transferred through a WiFi network to the end user. The user could also control and move the robot in different directions for specific demands. The designed simple robot interests users to record and transfer information for the safety of their indoors.